(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Women’s World: Journal of Serbian Women’s Charity Associations was edited by Arkadije Varadjanin since 1886 until 1914. Basic information about the journal, its editor and the foundation of charity associations in Vojvodina is followed by a bibliography which refers to the first five years of publication (1886-1890) and contains 659 bibliographical units described de visu.